2020
DOI: 10.1186/s42077-020-00104-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between intranasal dexmedetomidine and intranasal ketamine as a premedication for anxiolysis and sedation before pediatric general anesthesia

Abstract: Background This study compared dexmedetomidine versus ketamine as regard sedation and anxiolysis produced by giving them through intranasal route to pediatric patients undergoing adenotonsillectomy. This study was double-blinded randomized comparative prospective interventional clinical study done in Ain Shams University Hospital (El Demerdash Hospital) on 76 pediatric patients who underwent adenotonsillectomy, and they were randomly allocated equally into two main groups; group D received 2 μg/kg intranasal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Regarding the secondary outcomes, the detailed comparisons of the efficacies of different drugs were as presented in Appendix A7. Table 2 shows the interventions, the number of trials and participants, and the results of the secondary outcomes (incidence of ED, 8,24,26–28,30,31,33,48,49,52–63 incidence of PONV in PACU, 23,28,31,38,41,42,55,59,61–64 need for rescue analgesia in PACU, 31,38,41,53,55,59,62,63,65 length of stay in PACU, 29,31,39,40,52–54,57–59,61–63,65 changes in SBP after interventions, 23,40,50,51,57,66,67 changes in HR after interventions, 8,23,25,26,40,50,51,53–55,57,64,66–68 and changes in SPO 2 after intervention 8,23,40,51,64 ). Individual rank plots and SUCRA for the secondary outcomes were as shown in Appendices A9 and A10.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the secondary outcomes, the detailed comparisons of the efficacies of different drugs were as presented in Appendix A7. Table 2 shows the interventions, the number of trials and participants, and the results of the secondary outcomes (incidence of ED, 8,24,26–28,30,31,33,48,49,52–63 incidence of PONV in PACU, 23,28,31,38,41,42,55,59,61–64 need for rescue analgesia in PACU, 31,38,41,53,55,59,62,63,65 length of stay in PACU, 29,31,39,40,52–54,57–59,61–63,65 changes in SBP after interventions, 23,40,50,51,57,66,67 changes in HR after interventions, 8,23,25,26,40,50,51,53–55,57,64,66–68 and changes in SPO 2 after intervention 8,23,40,51,64 ). Individual rank plots and SUCRA for the secondary outcomes were as shown in Appendices A9 and A10.…”
Section: Resultsmentioning
confidence: 99%
“…They reported greater sedation at 10, 20 and up to 30 min with intranasal dexmedetomidine assessed using a modified Ramsay sedation score with comparable ease of parental separation. [25][26][27] Dexmedetomidine activates the non-rapid eye movement sleep-promoting pathway leading to a state closely resembling natural physiological sleep thus producing a potent sedative effect and facilitating parental separation. 14 Whereas, ketamine induces a dissociative anaesthetic state where the child is awake but disorientated.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with recent studies which demonstrated the superior sedative efficacy of intranasal dexmedetomidine (2–2.5 μg kg −1 ) when compared to intranasal ketamine (5 mg kg −1 ) administered using calibrated droppers and syringes. They reported greater sedation at 10, 20 and up to 30 min with intranasal dexmedetomidine assessed using a modified Ramsay sedation score with comparable ease of parental separation 25–27 …”
Section: Discussionmentioning
confidence: 99%